Evaluation of light transmission and uniformity of hardening of resin cements as a function of simulated indirect restoration thickness - Souza, Luana dos Santos; Osório, Sandy Vitória dos Santos; Monnerat, Maria Fernanda; Caneppele, Taciana Marco Ferraz; Bresciani, Eduardo (Brazilian Dental Science, 2025)
Objective: This study evaluated how the thickness of a simulated indirect restoration influences the light transmission of curing units and the uniformity of dual-cure resin cement polymerization using two light sources. (VALO – ULTRADENT and RADII-CAL – SDI). Material and Methods: Sixty A2-shade resin composite discs (GrandioSo, VOCO GmbH), 12 mm in diameter, were fabricated and divided into three experimental groups by thickness: 1.5 mm, 2.5 mm, and 3.5 mm (n = 10 per group). For irradiance transmission, light passage through each disc was measured using a radiometer (ECEL RD-7). The same discs were used in an indirect restoration simulation (SRI), employing a 3D-printed mold with 0.3 mm lateral barriers to ensure uniform cement thickness. Dual-cure resin cement (Bifix QM Universal, VOCO GmbH) was applied, and light-curing was performed for 60 seconds with each light source. After 24 hours, Knoop microhardness was assessed in three regions of the cement: central, intermediate, and peripheral region. Light transmission was analyzed by two-way ANOVA, while cement microhardness was assessed by three-way ANOVA, followed by Tukey’s post-hoc test (α=0.05). Results: Light transmission was undetectable through 3.5 mm specimens, indicating increased attenuation with thickness. VALO showed higher irradiance (67.6 ± 9.69 mW/cm2) than RADII-CAL (57.3 ± 13.82 mW/cm2). Cement microhardness decreased as restoration thickness increased, with the highest value at 1.5 mm using VALO (75.4 ± 8.43). Thickness also influenced hardening uniformity, with the highest regional value observed in the center of 1.5 mm specimens (81.5 ± 6.49). Conclusion: We can conclude that thickness directly influences the hardening of dual-cure resin cement, as it is affected by the light attenuation occurring through the indirect restorative material. KEYWORDS Cementation; Dental materials; Polymerization; Prosthodontics; Resin cements.